Incidencia e identificación de Trichomonas en trabajadoras sexuales que asisten al Centro de Salud Dra. Mabel Estupiñán de la ciudad de Machala de septiembre diciembre del 2006 . - Tandazo Seminario, Shirley M (2008)
The main manifestation of vaginal infection by a parasite known with the name of Trichomona vaginalis, is the vaginal secretion that by the general are accompanied by ardor and picazón of the vagina although not always bulb vaginal alterations in urethra and glands appears, in many occasions there is ardor when tinkling and in the vagina orifice.